The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1084/jem.193.7.803
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Attenuate T Cell Receptor Signaling

Abstract: Glucocorticoids (GCs) affect peripheral immune responses by inhibiting T cell immunity at several stages of the activation cascade, causing impaired cytokine production and effector function. The recent demonstration that the thymic epithelium and possibly thymocytes themselves produce steroids suggests that endogenous GCs also play a role in the control of T cell development. As both peripheral responsiveness and thymic differentiation appear to be regulated by the quantity and quality of intracellular signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 82 publications
4
83
1
1
Order By: Relevance
“…There are numerous in vivo and in vitro reports on corticosteroids and their analogues which effect thymocyte apoptotsis and which also have adverse effects on peripheral T cell activation events. [76][77][78][79][80][81][82] However, a previous study by Wienberg et al 34 demonstrated that TREC levels increased in cord blood transplant recipients even while receiving low-dose steroids as GVHD prophylaxis. However, this data does not exclude the possibility that high dose corticosteroids used in GVHD treatment would have an adverse effect on thymic output.…”
Section: Discussionmentioning
confidence: 88%
“…There are numerous in vivo and in vitro reports on corticosteroids and their analogues which effect thymocyte apoptotsis and which also have adverse effects on peripheral T cell activation events. [76][77][78][79][80][81][82] However, a previous study by Wienberg et al 34 demonstrated that TREC levels increased in cord blood transplant recipients even while receiving low-dose steroids as GVHD prophylaxis. However, this data does not exclude the possibility that high dose corticosteroids used in GVHD treatment would have an adverse effect on thymic output.…”
Section: Discussionmentioning
confidence: 88%
“…Similar disturbances of membrane rafts involving the displacement of Src family kinases and LAT apparently also contribute to the glucocorticoid-mediated inhibition of T cell signaling (50). Because dietary PUFAs are effectively incorporated into lymphocyte membrane lipids, altered LAT membrane subdomain distribution could also underlie the clinically apparent immunosuppressive action of PUFAs when these substances are applied to patients with inflammatory diseases.…”
Section: Pag-lat Chimeric Protein Is Retained In Rafts Of Pufaenrichementioning
confidence: 99%
“…Their mechanism of action is diverse and includes interference with intracellular transcription factors and signaling pathways of several surface receptors, including the T cell antigen receptor 52 and downstream kinases. 53 High doses of corticosteroids (.1 mg/kg), used for induction therapy in transplantation, also induce lymphocyte apoptosis (including B cells) 46,54 and can prevent in vitro differentiation of B cells into plasma cells.…”
Section: Corticosteroidsmentioning
confidence: 99%